(4/9)^-3 × (-2/3)^3^this is for exponents powerplease do it i need to submit tmrw About the author Maya

Step-by-step explanation: [tex] {( \frac{4}{9} )}^{ – 3} \times {( \frac{ – 2}{3}) }^{3} = {( \frac{9}{4} )}^{3} \times {( \frac{ – 2}{3}) }^{3} = \frac{9 \times 9 \times 9 \times – 2 \times – 2 – 2}{4 \times 4 \times 4 \times 3 \times 3 \times 3} = \frac{ – 27}{8} [/tex] Reply

Step-by-step explanation:[tex] {( \frac{4}{9} )}^{ – 3} \times {( \frac{ – 2}{3}) }^{3} = {( \frac{9}{4} )}^{3} \times {( \frac{ – 2}{3}) }^{3} = \frac{9 \times 9 \times 9 \times – 2 \times – 2 – 2}{4 \times 4 \times 4 \times 3 \times 3 \times 3} = \frac{ – 27}{8} [/tex]